Extraction and Characterization of Cellulosic Nanowhisker Obtained from Discarded Cotton Fibers. (2015) - Nascimento, José Heriberto O. do; Luz, Rodrigo F.; Galvão, Felipe M.F.; Melo, José Daniel D.; Oliveira, Fernando R.; Ladchumananandasivam, Rasiah; Zille, Andrea
Abstract: This study aimed to characterize cellulose nanowhiskers extracted from discarded cotton fibers. The nanocellulose was characterized by dynamic light scattering, zeta potential, Scanning Transmission Electron Microscopy (STEM), Atomic force microscopy (AFM) and X-ray powder diffraction (XRD). The nanocrystals are characterized by a rod-like morphology with sizes between 100 nm and 300 nm. The acidic hydrolyses applied to the extract nanocrystals increased the crystallinity index from 72 to 86%. The average length and diameter obtained were 98.1±4.7 and 8.0±3.4 nm, respectively. The aspect ratio of the fibers, around 12.3, was lower than the values usually reported in the literature. The dynamic light scattering results were in accordance with the nano crystal dimensions showing an average size of 235 nm. Cellulose nanowhiskers obtained from cotton rejected by textile industry due to their abundance, low cost, high crystallinity, strength, low weight and biodegradability, are the ideal candidates for the processing of polymer nanocomposites.